Consciousness, theatre, literature and the arts 2015 - Meyer-Dinkgräfe, Daniel 1958- (Cambridge Scholars Publishing, 2016)
This book brings together essays based on papers presented at the 6th International Conference on Consciousness, Theatre, Literature and the Arts (CTLA), held from June 10 to 12, 2015, at St Francis College, Brooklyn Heights, New York. The conference was attended by seventy delegates from twenty countries across the world - the twenty-three essays collected here come from delegates from twelve of those countries. The range of contributions reflects the variety of material presented and discussed at the conference, across the fields of philosophy, literature, fine arts, music, dance, performance
Keywords: Psychologie; Interdisziplinarität; Literatur; Theater; Identität; Bewusstsein; Künste; Consciousness in art / Congresses; Arts / Psychological aspects / Congresses; Konferenzschrift; Konferenzschrift -- Brooklyn Heights, New York -- 2015